THE INFLUENCE OF FINANCIAL TECHNOLOGY (FINTECH) USAGE, FINANCIAL LITERACY, SAVING HABITS, AND CAPITAL STRUCTURE ON THE FINANCIAL CAPABILITY OF MSMES IN TANGERANG REGENCY - Nor Fatah Ulinnuha; Abu Naim; Sapriyadi; Andika Mugi Gumilang; Ervina Yennie Permananingrum; Mardi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
MSMEs in Tangerang Regency deal with a number of financial management issues, such as low financial literacy, poor saving practices, an uneven capital structure, and inefficient use of financial technology (Fintech). These circumstances affect MSMEs' limited ability to manage cash flow, secure capital, and sustain firm stability. This study aims to quantitatively analyse the influence of Fintech usage, financial literacy, saving habits, and capital structure on the financial capability of MSMEs in Tangerang Regency. The research method uses an associative approach with multiple regression analysis techniques applied to 200 MSME respondents selected through purposive sampling. The research instrument is a Likert scale that is evaluated using validity and reliability tests, while data analysis is carried out using SPSS using classical assumptions, t, and F tests. The study's findings indicate that the following variables—Fintech, financial literacy, kebiasaan menabung, and modal structure—have a positive and significant impact on UMKM's financial capabilities, both in a parallel and parallel manner. The Adjusted R-Squared value of 0.612 indicates that 61.2% of the financial variability can be explained by the developed model. This study highlights the importance of financial education, effective financial management, and the use of financial technology to increase UMKM's financial capabilities in the digital age. It is anticipated that this will serve as a catalyst for government agencies, financial institutions, and Fintech companies to develop more effective UMKM strategies